Preoperative Low-Density Lipoprotein Apheresis for Preventing Recurrence of Focal Segmental Glomerulosclerosis after Kidney Transplantation - Akihito Sannomiya; Toru Murakami; Ichiro Koyama; Kosaku Nitta; Ichiro Nakajima; Shohei Fuchinoue (Journal of Transplantation)
Background. Focal segmental glomerulosclerosis (FSGS) often develops rapidly and frequently progresses to renal failure, while the recurrence rate after kidney transplantation is 20–50%. We performed low-density lipoprotein (LDL) apheresis before kidney transplantation in FSGS patients to prevent recurrence. Methods. Five adult patients with chronic renal failure due to FSGS undergoing living related donor kidney transplantation were investigated retrospectively. LDL apheresis was done 1-2 times before transplantation. Postoperative renal function and recurrence of FSGS were assessed. Results. The patients were two men and three women aged 24 to 41 years. The observation period ranged from 60 days to 22 months. Preoperative LDL apheresis was performed once in one patient and twice in four patients. Blood LDL cholesterol levels were normal before LDL apheresis and remained normal both after LDL apheresis and after kidney transplantation. Additional LDL apheresis was performed once in one patient with mild proteinuria after transplantation. The renal graft survived in all patients and there was no evidence of recurrent FSGS. Conclusions. Although the observation period was short, FSGS did not recur in all 5 patients receiving preoperative LDL apheresis. These results suggest that LDL apheresis can be effective in preventing recurrence of FSGS after kidney transplantation.